2014
DOI: 10.1177/0003489414525335
|View full text |Cite
|
Sign up to set email alerts
|

Partial Mastoid Obliteration Combined With Soft-wall Reconstruction for Middle Ear Cholesteatoma

Abstract: The surgical outcomes of tympanoplasty with partial mastoid obliteration and soft-wall reconstruction for middle ear cholesteatoma were satisfactory with a low incidence of cholesteatoma recidivism and tolerable postoperative hearing without cavity problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
2
7
0
1
Order By: Relevance
“…(Edfeldt et al 2012, 2013, Gaillardin et al 2012, Møller et al 2020, van der Toom et al 2020. Hearing results were also in line with findings from other authors (Yung et al 2007, Suzuki et al 2014.…”
Section: Surgical and Hearing Outcomessupporting
confidence: 91%
“…(Edfeldt et al 2012, 2013, Gaillardin et al 2012, Møller et al 2020, van der Toom et al 2020. Hearing results were also in line with findings from other authors (Yung et al 2007, Suzuki et al 2014.…”
Section: Surgical and Hearing Outcomessupporting
confidence: 91%
“…A large number of researches have reported that if cholesteatomatous otitis media is not treated on time, the cholesteatoma will continue to increase, compress sclerotins and be absorbed, and the auditory ossicle will be injured. If bacteria enter into cranium, serious intracranial complications will occur, which may even lead to the patients death (17–19). There are no obvious specific symptoms in the early stage of cholesteatomatous otitis media, and its symptoms are easily confused with the clinical symptoms of patients with simple otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the classical CWD procedure with an open mastoid cavity, the emphasis of most studies has been on the management of postoperative chronic otorrhea [2,13,20,21,26]. Several partial or complete obliteration techniques with excellent anatomical results have been published [27,28,29,30]. …”
Section: Discussionmentioning
confidence: 99%